2010
DOI: 10.1074/jbc.m109.063941
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Membrane Structural Integrity for RPE65 Retinoid Isomerization Activity

Abstract: Regeneration of visual chromophore in the vertebrate visual cycle involves the retinal pigment epithelium-specific protein RPE65, the key enzyme catalyzing the cleavage and isomerization of all-trans-retinyl fatty acid esters to 11-cis-retinol. Although RPE65 has no predicted membrane spanning domains, this protein predominantly associates with microsomal fractions isolated from bovine retinal pigment epithelium (RPE). We have re-examined the nature of RPE65 interactions with native microsomal membranes by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 67 publications
4
78
0
1
Order By: Relevance
“…Also, substrates for CCOs are highly lipophilic and tend to reside in hydrophobic environments, such as plant thylakoid membranes (10) or liposomes in mammals (11)(12)(13). Accordingly, CCOs show varying levels of membrane association, from soluble to integral (14)(15)(16). ACO, VP14, and RPE65 all have surface-exposed hydrophobic patches in analogous regions that may serve as membrane interaction domains.…”
Section: Resultsmentioning
confidence: 99%
“…Also, substrates for CCOs are highly lipophilic and tend to reside in hydrophobic environments, such as plant thylakoid membranes (10) or liposomes in mammals (11)(12)(13). Accordingly, CCOs show varying levels of membrane association, from soluble to integral (14)(15)(16). ACO, VP14, and RPE65 all have surface-exposed hydrophobic patches in analogous regions that may serve as membrane interaction domains.…”
Section: Resultsmentioning
confidence: 99%
“…Purified RPE65 exhibited retinoid isomerase activity only when bound to all-trans-retinyl ester-incorporated membrane vesicles (10). Moreover, destruction of intact microsomal phospholipids by phospholipase A 2 greatly reduced the production of 11-cis-retinol by native bovine RPE65 (11). Spectroscopic data also indicated that RPE65 adopts functionally and structurally different conformations when bound to lipid bilayers compared with its detergent-solubilized state, although specific changes could not be ascertained (12).…”
mentioning
confidence: 99%
“…Historically, the inhibition of RPE retinoid isomerase activity by detergents was the major factor that delayed its link to RPE65, and the mechanism of inhibition remains incompletely understood. In the structure, we observed that residues composing the RPE65 membrane-interaction surface exhibit substantial disorder compared with the rest of the enzyme (11,13). Owing to the roles of these residues in membrane binding as well as substrate recognition and proper positioning of the substrate in the active site, detergent-induced alterations in their native structure, either by stripping the protein of its native phospholipids or by a direct effect, could inactivate the enzyme.…”
mentioning
confidence: 99%
“…Recent work concerning the three dimensional structure of B. taurus RPE65 protein [61][62][63][64] provides insight into reasons why the RPE65 F229S mutant protein may be nonfunctional and possibly unstable. The Rpe65 tvrm148 mutation resides in exon 7 of RPE65 1 and results in a substitution of Ser for Phe at amino acid position 229.…”
mentioning
confidence: 99%